An analysis of Marxist Essence: Present in Ghayoor Bukhari’s Saraiki Poetry - Sial, Imran Aslam (Pakistan Languages and Humanities Review, 2025)
The purpose of this research paper is to sight socio-political, financial literary understanding of the presumption of Marxism and finds the ideology is an economic philosophy and have roots in politics that highlight in the fundamental nature, the theory represents many facets such as outcome of production form of prosperity and its distribution and the reality of economic condition of the social order with the reference to Marxism fact-based reality. The theory highlights the endeavor to acquire power between rulers and ruled and disseminates the gentry’ difference in these two classes manipulating and manipulated. The aim of the theory is looking for parallel equality among people in order to manage class free society for the human being. In this way, the perspective of the philosopher, Karl Marx, Marxism is the development of the world consequently people would be beneficiary by practically applying such module and the earth is to alter by the revolution. In the circumstances of restructure: literature, society the world will unable to remain oblivious to the process. The poet Ghayoor Bukhari projects the panic conditions of deprived people of Saraiki Waseeb which consists of ‘Rohi’, ‘Thal’ and ‘Daman’. He brings light to the pitiful problems of Saraiki people such as hunger, starvation, and famine of society of emerging generation growing in quarters of working-class advising revolution in opposed to oppression. Ghayoor Bukhari singles handily make his reader see revolution and he himself turns the leading light who bears the flag of revolt and keep the positive hopes high. Moreover, supporters of Marxism and their deeds clearly admired by Ghayoor Bukhari and he also levelling them as remarkable icons.